Pengaruh Tekanan Anggaran Waktu, Konflik Peran, dan Ambiguitas Peran Terhadap Perilaku Disfungsional Audit - Novianne Devy, Arienda; Solikhah, Badingatus (Rifa'Institute, 2022)
The aims of this quantitative research is to testing the effect of time budget pressure, role conflict, and role ambiguity on dysfunctional audit behavior at APIP in the Central Java Provincial Inspectorate. All of APIP employees that totaling 63 peoples became the population, and 61 of them were taken as samples with saturated sampling method. The data were collected using questionnaire, observation, and documentation methods. Data analysis was carried out descriptively and inferentially used the Smart PLS 3.0 model. The results showed that the effect of time budget pressure on dysfunctional audit behavior was significant with a path coefficient of +0,255 and a probability value (p) 0,003 < 0,05. Then the effect of role conflict on dysfunctional audit behavior was significant with a path coefficient of +0,433 and a probability value (p) 0,000 < 0,05. And the effect of role ambiguity on dysfunctional audit behavior was significant with a path coefficient of +0,303 and a probability value (p) 0,008 < 0,05. So it can be concluded that the factors influenced the dysfunctional audit behavior of APIP at the Central Java Provincial Inspectorate is time budget pressure, role conflict, and role ambiguity.